Kajian Hukum Terhadap Bahaya Pengumpulan Informasi Rekayasa Sosial Melalui Fitur Add Yours Instagram - Novitasari, Nanda Silvia; Tantimin, Tantimin (Fakultas Syariah INSURI Ponorogo, 2023)
The development of information technology has changed human behavior and increased performance and productivity because it allows various activities to be carried out quickly, precisely, and accurately. As technology develops, the use of social media is also growing. The Addyourss feature on Instagram Stories is based on user-generated content and should positively impact broader engagement on Instagram; however, in Indonesia, this feature is abused by irresponsible parties, causing problems. Fraud and misuse of personal identity. This study is designed to analyze legal research on the dangers of collecting information on psychological manipulation by adding your Instagram capabilities and to analyze the extent to which the government provides legal protection for personal data against data misuse, personal data on social media platforms based on the ITE Law and what legal actions what victims can do about misuse of personal data on social media platforms. This qualitative research uses the natural environment to explain what happened and was carried out by involving existing methods. The findings of this study indicate that legal protection of personal data against misuse of personal data on social media platforms still needs to be improved and comprehensive. Establishing a clear and comprehensive law is urgently needed to identify clear steps in using personal data to provide legal certainty for protecting public personal data. According to the law, legal action for victims of misuse of personal data on social media platforms is still limited to filing lawsuits and demanding administrative penalties.